New 1,3,4-thiadiazoles based on thiophene-2-carboxylic acid: Synthesis, characterization, and antimicrobial activities - Muğlu, Halit; Yakan, Hasan; Shouaib, Hanan Almabrok (Elsevier BV, 2020)
Abstract Novel 1,3,4-thiadiazole derivatives were prepared by cyclization reaction of thiophene-2-carboxylic acid with N-arylthiosemicarbazides and POCl3. The antibacterial activities of the synthesized compounds were tested against Gram-negative bacteria (Salmonella enteritidis, Salmonella typhimurium, Enterobacter aerogenes, Salmonella infantis, Salmonella kentucky, and Escherichia coli), Gram-positive bacteria (Staphylococcus aureus, Bacillus subtilis, and Enterococcus durans), and the fungus Candida albicans using the disk diffusion method. Selected 1,3,4-thiadiazole derivatives exhibited effective antimicrobial activity against S. aureus, C. albicans, S. typhimurium, E. aerogenes, and S. kentucky. Therefore, 1,3,4-thiadiazole derivatives can be considered as bioactive agents for pharmacological and medicinal applications. The synthesized compounds were characterized by using IR, 1H NMR, and 13C NMR spectroscopies and elemental analysis.
Keywords: Thiophene-2-carboxylic acid; ,3,4-Thiadiazoles; N-arylthiosemicarbazides; Spectroscopic methods; Antimicrobial activity; 3. Good health